Arginine vasopressin and copeptin: comparative review and perspective in veterinary medicine - Paulin, Mathieu Victor; Schermerhorn, Thomas; Unniappan, Suraj; Snead, Elisabeth C. R. (Frontiers in Veterinary Science, 2025)
Although arginine vasopressin (AVP) deficiency, AVP resistance, and primary polydipsia are important causes of polyuria and polydipsia (PUPD), measurement of AVP has never been implemented as a routine diagnostic test for patient care in either human or veterinary medicine, due to significant challenges with the methodologic reliability of laboratory assays for measuring AVP. Responses to a modified water deprivation test and/or a desmopressin acetate trial have been used as indirect markers of AVP deficiency or resistance. However, interpretations of these tests can be especially challenging in cases of partial AVP deficiency or resistance. Over the past decade, plasma copeptin (CoP), a glycopeptide comprising the C-terminal part of the AVP preprohormone, has mostly replaced AVP measurement in humans. When combined with CoP-based stimulation tests, such as hypertonic saline and arginine stimulation tests, plasma CoP measurement offers excellent diagnostic accuracy for the diagnosis and differentiation of cases of central diabetes insipidus (DI), nephrogenic DI, and primary polydipsia in humans. In dogs, CoP has recently been measured in saliva and serum using canine or human enzyme-linked immunosorbent assays. This review will provide an update on the physiologic regulation of AVP production and secretion, the limitations of its measurement in human and veterinary medicine, as well as a summary of the indications and performance of CoP measurement in human and veterinary medicine to date. This is with a purpose to encourage validation and implementation of CoP measurement in veterinary medicine.